1979
DOI: 10.3177/jnsv.25.205
|View full text |Cite
|
Sign up to set email alerts
|

Influences of oyster or clam feeding on lipid metabolism in rats.

Abstract: SummaryRats were fed on three kinds of diets for two weeks: (I) basal diet, (II) containing 0.1% cholate and (III) containing 0.1% cholesterol and 0.1% cholate. Each dietary group was further divided into subgroups to whose diet was added 0, 5 or 10% (dry weight) of minced oyster (Callocorchina) or clam (Tapes japonica). The serum and liver cholesterol levels of the rats fed the basal diet were reduced by feeding oyster or clam. The serum and liver triglyceride levels of all dietary groups were lowered markedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Sulfate polysaccharide extracted from abalone gonads improves the ecological imbalance of the intestinal flora, inhibits the expression of the GPR43 gene in adipose tissue, and increases GPRA41 expression in mice fed with a high-fat diet, preventing weight gain and fat accumulation (Liu et al, 2019). Supplementation with oyster in the diet exhibits a hypolipidemic effect in rats fed with both a normal diet and a high-cholesterol diet (Iritani et al, 1979). Our objective is to evaluate the potential hypolipidemic effect of glycosaminoglycans from Ostrea rivularis (OGAG) and the mechanism underlying such effect.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfate polysaccharide extracted from abalone gonads improves the ecological imbalance of the intestinal flora, inhibits the expression of the GPR43 gene in adipose tissue, and increases GPRA41 expression in mice fed with a high-fat diet, preventing weight gain and fat accumulation (Liu et al, 2019). Supplementation with oyster in the diet exhibits a hypolipidemic effect in rats fed with both a normal diet and a high-cholesterol diet (Iritani et al, 1979). Our objective is to evaluate the potential hypolipidemic effect of glycosaminoglycans from Ostrea rivularis (OGAG) and the mechanism underlying such effect.…”
Section: Introductionmentioning
confidence: 99%
“…Since the oyster diets contained 0.21% non-cholesterol sterols, at least a part of the increase of fecal neutral steroid excretion may be ascribed to the non-cholesterol sterols. Iritani et al also reported that the hepatic cho lesterogenic enzyme activity was decreased in rats fed oyster as compared to rats fed a casein-based control diet (8). Therefore, the decrease of hepatic cholesteroge nesis may be another cause of the reduced hepatic cho lesterol concentration in the feeding of oyster.…”
Section: Resultsmentioning
confidence: 96%
“…Iritani et al showed that the activities of glucose-6-phosphate dehydrogenase, malic enzyme and acetyl-CoA carboxylase in the liver of rats were reduced by the feeding of oyster (8). Therefore, the decrease of hepatic triglyceride level in the rats fed oyster is consid ered to be in part induced by the reduction of lipogene sis in the liver.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WEC contains high levels of free amino acids, glycogen, vitamins, and mineral substances which mediate many physiological functions (Peng et al, 2008;Watanabe et al, 2001;Wohlt et al, 1994). Previous studies have shown that WEC has beneficial effects such as reducing fatty acid and cholesterol synthesis, thus helping to prevent cardiovascular diseases (Childs et al, 1990;Iritani et al, 1979). It also increased immunity and reduced tumor incidence in rodents inoculated with the adenovirus (Li et al, 1972).…”
Section: Introductionmentioning
confidence: 99%